2014
DOI: 10.1159/000360077
|View full text |Cite
|
Sign up to set email alerts
|

Basal Serum Thyroglobulin Measured by a Second-Generation Assay Is Equivalent to Stimulated Thyroglobulin in Identifying Metastases in Patients with Differentiated Thyroid Cancer with Low or Intermediate Risk of Recurrence

Abstract: Background: Guidelines for the follow-up of differentiated thyroid cancer (DTC) recommend the measurement of TSH-stimulated thyroglobulin (s-Tg) instead of basal Tg on T4 therapy (b-Tg). However, these guidelines were established using first-generation Tg assays with a functional sensitivity (FS) of 0.5-1.0 ng/ml. Current more sensitive second-generation Tg assays (Tg2G; FS 0.05-0.10 ng/ml) have shown that low-risk DTC patients with undetectable b-Tg rarely have recurrences. Objectives: This study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…showed that even patients with indeterminate response to therapy had a good prognosis, with no evidence of structural disease during follow-up, and could be observed conservatively (4,9,11,29). Current second generation Tg assays (0.05-0.1 ng/mL) have shown that patients with lowrisk DTC with undetectable baseline Tg rarely recur (5). In this sense, study published in 2016 by Janovsky (1) concluded that an excellent response to treatment can be confirmed by the trend of Tg and US, these being the best follow-up approaches, showing that the use of RRA only to achieve negative levels of Tg for surveillance is not necessary because it is not an isolated value, but the tendency of Tg during follow-up, the determining factor for both (1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that even patients with indeterminate response to therapy had a good prognosis, with no evidence of structural disease during follow-up, and could be observed conservatively (4,9,11,29). Current second generation Tg assays (0.05-0.1 ng/mL) have shown that patients with lowrisk DTC with undetectable baseline Tg rarely recur (5). In this sense, study published in 2016 by Janovsky (1) concluded that an excellent response to treatment can be confirmed by the trend of Tg and US, these being the best follow-up approaches, showing that the use of RRA only to achieve negative levels of Tg for surveillance is not necessary because it is not an isolated value, but the tendency of Tg during follow-up, the determining factor for both (1).…”
Section: Discussionmentioning
confidence: 99%
“…O ver the last decades, the incidence of DTC has increased significantly, especially of tumors smaller than 2 cm (1)(2)(3). Despite this, most of these patients have an excellent prognosis and a long followup during their lifetime (4,5). Nevertheless, rarely small tumors can metastasize and have an increased recurrence risk (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…For low-risk thyroid cancer, studies suggest using 30 mCi for RRA, with the aim of achieving negative Tg levels for accurate surveillance [11,31,32] . Our study shows that the use of RRA just to turn Tg into an accurate marker is not necessary, because it is not a single Tg value that most matters, but rather the Tg trend during the follow-up, as others have also demonstrated [33,34] .…”
Section: Discussionmentioning
confidence: 76%
“…David A et al demonstrated that every rhTSH/Tg concentration increase over 1.0 ng/ml may indicate a relapse or a persistent disease. The increase in the rhTSH/Tg level to 1.0–5.0 ng/ml in the study group analyzed by the authors was linked to the presence of metastases in 30% of the patients and an increase in the value to over 5.0 ng/ml up to 81% [ 24 ]. The increase of the rhTSH/Tg level to over 1.0 ng/ml in our material was observed in all patients with the diagnosed persistent disease and in 4 out of 49 patients with ineffective ablation without any other disease foci in the image tests.…”
Section: Discussionmentioning
confidence: 99%